Target-triggered autonomous assembly of DNA polymer chains and its application in colorimetric nucleic acid detection. Issue 19 (5th April 2016) - Dai, Jianyuan; He, Hongfei; Duan, Zhijuan; Zhou, Cuisong; Long, Yuyin; Zheng, Baozhan; Du, Juan; Guo, Yong; Xiao, Dan
Abstract : One-dimensional DNA polymer chains were obtained based on the catalyzed hairpin assembly and sticky end self-assembly, which led to a signal amplified colorimetric nucleic acid assay. Abstract : A novel target-triggered DNA autonomous assembly pathway for the formation of one-dimensional DNA polymer chains was proposed based on the catalyzed hairpin assembly and sticky end self-assembly, which led to an enzyme-free and signal amplified gold nanoparticle (AuNP) based colorimetric nucleic acid assay with picomolar sensitivity and specificity.